(untitled) (Docentes 2.0 Journal, 2023)
The educational processes have been changing, updating the tools and strategies to facilitate student learning, from respect for diversity in the classroom and focused on meeting educational needs. The study’s objective was to analyze digital intelligence tools to strengthen the academic writing of high school students. The research was based on the deductive method, positivist paradigm, mixed approach, documentary design, and exploratory type, highlighting the relevant aspects of research. The universe comprised a population of 200 high school students and a sample of 81, chosen by non-probability sampling for convenience. A validated survey was used as a data collection technique, for which a Cronbach’s Alpha of 0.76 was generated. The survey questionnaire consisted of 5 multiple-choice items with a Likert scale. The respective analysis and interpretation of results was carried out using the SPSS program, obtaining as a main result that the high school students of the Juan Antonio Vergara Alcívar Educational Unit have a medium and low level of writing skills even though writing tools are applied. Artificial intelligence, concluding that artificial intelligence tools favor academic writing skills as long as students have developed skills for effectively managing technology.